Effects of increased temperature on atmospheric pollutant levels and human health in small and medium-sized cities in southern Brazil - Rodrigo de Lima Brum; Júlia Oliveira Penteado; Ronan Adler Tavella; Willian Cézar Nadaleti; Aline Neutzling Brum; Ng Haig They; Mariana Vieira Coronas; Roberta Daniele Klein; Natália Pereira; Flavio Manoel Rodrigues da Silva Júnior (Case Studies in Chemical and Environmental Engineering)
This study analyzed the impact of temperature increases on O3, PM2.5, and PM10 concentrations and cardiopulmonary deaths attributable to PM2.5 in 11 cities in southern Brazil, including Porto Alegre. In 2022, 12.80 % of cardiopulmonary deaths in the capital were attributed to PM2.5. Although small cities were within legal limits, simulated scenarios of +2 and + 4 °C indicated an increase in deaths in all cities. The results highlight the need for public health interventions and climate adaptation strategies to mitigate the impacts of pollution and global warming in smaller cities.